Global Space Governance : Africa's contribution to the United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) - Pretorius, E.P. (University of Pretoria, 2019)
Mini Dissertation (MDiplomatic Studies)--University of Pretoria, 2019.